Determinan Kinerja Pengelolaan Keuangan Desa: Studi pada Kecamatan Gandapura Kabupaten Bireuen Aceh - Munti, Finta; Fahlevi, Heru (Universitas Muhammadiyah Yogyakarta, Indonesia, 2017)
The purpose of this study is to investigate the determinants of Village Financial Management Performance in Gandapura village in the District of Bireuen - Aceh. The tested variables are village officers’ capacity, financial reporting compliance and supervision quality of Badan Permusyawaratan Desar (BPD). The population is all village within Gandapura district, Bireuen, which consists of 40 villages in total. This study involved all the population as the sample. Seletected respondents are Keuchik (or head of villages), village treasurers, Tuha Peut (or village legislative/supervision board) and village facilitators. The data collected through questionaraires and analysed by using multiple linear analysis. This study uncovered an empirical evidence on the effect of village officers’ capacity, financial reporting compliance and supervision quality both collectively and indivdually on the village Financial Management Performance.